Orange juice improved lipid profile and blood lactate of overweight middle-aged women subjected to aerobic training - Aptekmann, Nancy Preising [UNESP]; César, Thaís Borges [UNESP] (Elsevier B.V., 2010)
Objective This study investigated how consumption of orange juice associated with aerobic training affected serum lipids and physical characteristics of overweight middle-aged womenMethods The experimental group consisted of 13 women who consumed 500 mL/d of orange juice and did 1 h aerobic training 3 times a week for 3 months The control group consisted of another 13 women who did the same aerobic training program but did not consume orange juiceResults At the end of the experiment the control group lost an average of 15% of fat mass (P < 0 05) and 25% of weight (P < 0 05) whereas the experimental group lost 11% of fat mass and 1 2% of weight (P < 0 05) Consumption of orange juice by the experimental group was associated with Increased dietary intake of vitamin C and folate by 126% and 61% respectively Serum LDL-C decreased 15% (P < 0 05) and HDL-C increased 18% (P < 0 05) in the experimental group but no significant change was observed in the control group Both groups improved the anaerobic threshold by 20% (P < 0 05) but blood lactate concentration decreased 27% in the experimental group compared to the 17% control group suggesting that experimental group has less muscle fatigue and better response to trainingConclusions The consumption of 500 mL/d of orange juice associated with aerobic training in overweight women decreased cardiovascular disease risk by reducing LDL-C levels and increasing HDL-C levels This association also decreased blood lactate concentration and increased anaerobic threshold showing some improvement in the physical performance (C) 2010 Elsevier B.V. All rights reserved
Keywords: Orange Juice; Aerobic training; Lipid profile; Blood lactate concentration; Middle aged women; Anaerobic thieshold